FORMULASI DAN KARAKTERISTIK COOKIES BERBASIS TEPUNG DAUN KELOR DAN TEPUNG UDANG PUTIH SEBAGAI ALTERNATIF MAKANAN SELINGAN TINGGI ZAT BESI UNTUK ANEMIA PADA REMAJA - Alvionita, Dinda; Priawantiputri, Witri; Gumilar, Mulus; Hapsari, Agustina Indri (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2022)
Cookies are one of the most popular food products for people of all ages. Cookies are used as an alternative snack for anemia in adolescents with the main ingredients, namely Moringa leaf flour and white shrimp flour which are high in iron and protein. This study aims to obtain a formulation and determine the effect of Moringa leaf flour and white shrimp flour on the quality of cookies products which include organoleptic properties and levels of nutrients (iron and protein). The research design used was experimental with a completely randomized design. The research method used is hedonic test to determine organoleptic properties involving 30 panelists, Atomic Absorption Spectrophotometry (AAS) method to test iron levels, and micro kjeldahl method to test protein levels. Cookies formulation obtained 3 different formulas, namely F1 (45%:5%), F2 (40%:10%) and F3 (35%:15%). The results of thetest Kruskall Wallis showed that there was no significant difference in the aspects of color, taste, aroma, texture, and overall. Formula F2 excels in terms of color, taste, and overall. The results of the iron content test were obtained by formulas F1, F2, F3 which were 0.239 mg/100 gr, 0.221 mg/100 gr, 0.204 mg/100 gr and the protein content test obtained formulas F1, F2, F3 which was 6.96 gr/100 gr, 7.35 gr/100 gr, 8.13 gr/100 gr. Suggestions for further research are the need for changes in the procedure for making Cookies in order to obtain an attractive appearance of Cookies, especially in the aspects of color, taste and shape and the need for further research on the effect of giving Cookies based on Moringa leaf flour and white shrimp flour on adolescents, especially young women.